Teori Labeling dalam Perspektif Kebijakan Kriminal : Strategi Dekriminalisasi untuk Menghentikan Siklus Stigma Sosial - Zul Khaidir Kadir (Jurnal Hukum dan Sosial Politik, 2025)
Labeling theory provides a critical perspective on the criminal justice system that tends to reinforce criminal identities through formal labeling. Unfortunately, criminal policies that are ideally designed to manage crime and maintain social stability often result in negative impacts such as stigmatization. This study explores the integration of labeling theory and decriminalization as a more inclusive and social justice-based criminal policy approach. The research method used is a qualitative research method with a conceptual approach. The results of the study indicate that decriminalization prevents formal labeling that is the root of the cycle of social stigma. In addition, decriminalization provides opportunities for individuals to remain integrated into society, increases their access to health services and rehabilitation programs, and creates more inclusive social conditions. However, the success of decriminalization depends heavily on the government's ability to overcome various inherent challenges, including cultural resistance, concerns about policy abuse, and limited supporting infrastructure.